2020
DOI: 10.1063/5.0022428
|View full text |Cite
|
Sign up to set email alerts
|

Geometric and control optimization of a two cross-flow turbine array

Abstract: Cross-flow turbines, also known as vertical-axis turbines, convert the kinetic energy in moving fluid to mechanical energy using blades that rotate about an axis perpendicular to the incoming flow. In this work, the performance of a two-turbine array in a recirculating water channel was experimentally optimized across 64 unique array configurations. For each configuration, turbine performance was optimized using tip-speed ratio control, where the rotation rate for each turbine is optimized individually, and us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 45 publications
1
7
0
Order By: Relevance
“…Combining these two methods resulted in enhancing turbine performance by 24.9% for two array turbines. The successful implementation of RPM control for optimal operation of two-array VAWTs was also shown by Scherl et al [23] using experiments.…”
Section: Introductionsupporting
confidence: 52%
“…Combining these two methods resulted in enhancing turbine performance by 24.9% for two array turbines. The successful implementation of RPM control for optimal operation of two-array VAWTs was also shown by Scherl et al [23] using experiments.…”
Section: Introductionsupporting
confidence: 52%
“…Finally, for a fixedwidth channel, changing D changes both the spacing between adjacent turbines as well as the proximity of the turbines at the ends of the array to the channel side walls. For proximity on the order of the blade chord length, this alters the hydrodynamic interactions between adjacent rotors [36] as well as the lateral boundary effects on array performance [28].…”
Section: Introductionmentioning
confidence: 99%
“…Cooke et al (2015) conducted experiments in a wide channel with porous disks to emulate turbines to explore the principles of the partial fence theory of Nishino & Willden (2012) and determined that local constructive interference effects can be used to support higher disk thrusts in closely spaced arrays, leading to greater power extraction in the case of turbines. Scherl et al (2020) performed experiments for two vertical axis turbines varying the cross-stream and streamwise inter-turbine spacing in 64 different configurations. They concluded that a cross-stream arrangement, in which turbines are arrayed co-planar, provided the best performance enhancement, with diminishing performance as the streamwise separation increased and one turbine entered the wake of the other, relaxing local blockage effects.…”
Section: Introductionmentioning
confidence: 99%